2D holodirected lead(II) halide coordination polymers based on rigid N, N′-bis(4-pyridylmethylidyne) phenylene-1, 4-diamine ligand: Syntheses, crystal structures, NBO studies and luminescence properties. (17th June 2017) - Rad-Yousefnia, Negar; Shaabani, Behrouz; Kubicki, Maciej; Zakerhamidi, Mohammad Sadegh; Grzeskiewicz, Anita M.
Graphical abstract: We report preparation of three lead(II) coordination polymers, [Pb(µ-L)(µ-Cl)2 ] n (1 ), [Pb(µ-L)(µ-Br)2 ] n (2 ), and [Pb(µ-L)(µ-I)2 ] n (3 ), (L = N, N′-bis(4-pyridylmethylidyne) phenylene-1, 4-diamine). Compounds1 –3 were characterized by FT-IR and single crystal X-ray diffraction techniques. Subsequently, thermal and luminescent properties and also NBO studies were investigated. Abstract: To investigate the influence of the different halides on coordination parameters and exploitable properties, a series of isostructural lead(II) coordination polymers, namely, [Pb(µ-L)(µ-X)2 ] n (X = Cl (1 ), Br (2 ), I (3 )) based on rigid ligand N, N′-bis(4-pyridylmethylidyne) phenylene-1, 4-diamine (L) were synthesized successfully. The structures of these compounds were elucidated by FT-IR spectroscopy, and single crystal X-ray diffraction crystallography. Single crystal X-ray analyses revealed that these compounds have a 2D net structure containing PbX4 N2 centers in which lead(II) ions bridged by both halide anions and L ligands in trans arrangement. Moreover, natural bond orbital (NBO) calculations were employed to obtain atomic charge distributions, hybridizations and the strength of interactions between lead ion and halides via second-order perturbation energies. All materials display a blue luminescence in the solid state at room temperature. Also, there is an obvious relationship between the NBO findings and observed red shift order in these compounds. Finally the results of thermal behavior studies of compounds1 –3 have been discussed.